Integrating Collaborative and Live Coding for Distance Education. - Ghorashi, Soroush; Jensen, Carlos (Computer (00189162), 2017)
What does an online programming course need to engage students and improve their skills? To answer this question, the authors designed and tested a feature-rich collaborative environment for an online class and found that it enhanced learning through methods such as remote pair programming, live coding, and a tight code-to-artifact feedback loop.